Implementing Active Learning through Practical Methods to Enhance Scientific Literacy - Muhammad Ridho Avicenna; Ihsan Rizkyansah Akhmad; Muhammad Firgio Dafa Al-Mawangsyah; Trias Setyowati; Dzikrina Aqsha Mahardika (Asosiasi Lembaga Pendidikan Tenaga Kependidikan Peguruan Tinggi Muhammadiyah dan Aisyiyah, 2023)
Education is a fundamental right guaranteed by law for all children. However, not all children can enjoy a quality education, especially Indonesian Migrant Worker (TKI) children living abroad. To assist these children, various tutoring centers have been established as alternative educational solutions. However, research indicates that tutoring centers alone are not sufficiently effective in addressing educational issues. One of the main challenges is the low interest and motivation of children towards education. Therefore, an innovative solution is needed to achieve the ultimate goal of fulfilling education. This research aims to evaluate the effectiveness of implementing active learning with a practical approach to enhance scientific literacy among children in the Hulu Klang tutoring center. Using a descriptive and qualitative approach, the researcher collected data through observations for approximately one month as part of the KKN KI MBKM PTMA program. The findings indicate a positive trend in improving scientific literacy among children. This is evident from the enthusiasm of the children in participating in practical activities, such as building water rockets, generating electricity from fruits, and creating simple compasses. These activities are designed to encourage children to think critically and seek solutions through scientific literacy.